Study protocol: long-term effect of the New Nordic Renal Diet on phosphorus and lipid homeostasis in patients with chronic kidney disease, stages 3 and 4: a randomised controlled trial - Arne Astrup; Bo Feldt-Rasmussen; Nikita Misella Hansen; Marianne Rix; Anne-Lise Kamper; Christina Christoffersen; Louise Salomo (BMJ Open)
Introduction Chronic kidney disease (CKD) causes severe disturbances in phosphate metabolism. New Nordic Renal Diet (NNRD) is a new dietary concept designed by the present research group that aims to offer patients with moderate CKD a whole food approach with a markedly reduction in dietary phosphorus intake, corresponding to 850 mg/day. The present protocol describes a randomised controlled trial aiming to test the long-term effects of dietary intervention with NNRD versus a non-restricted habitual diet on important parameters of phosphorus and lipid homeostasis.Methods and analysis This trial will be executed at the Department of Nephrology, Rigshospitalet, University of Copenhagen, Denmark. Sixty patients aged >18 years with CKD stages 3 and 4 (estimated glomerular filtration rate between 15 and 45 mL/min) will be recruited and randomly assigned to the intervention or control group. The other inclusion criterion includes a medically stable condition for at least 2 months prior to the start of the study. Exclusion criteria are treatment with phosphate binders, metabolic disorders that require specific dietary regulation, pregnancy and breast feeding, any types of food allergies or those who are vegans. The observation period is 26 weeks including seven study visits at the outpatient clinic combined with a weekly telephone consultation in both groups. A follow-up visit 3 months after study completion finalises the intervention. The primary outcome is the difference in the change in 24-hour urine phosphorus excretion from baseline to week 26 between the two study groups. Secondary outcomes include changes in phosphate-related and lipid metabolism-related blood and urine biochemistry, blood pressure and body composition. Moreover, we wish to explore adherence to the diet as well as quality of life.Ethics and dissemination The study has been approved by the Scientific Ethical Committee of the Capital Region of Denmark and the Danish Data Protection Agency. The results of the studies will be presented at national and international scientific meetings, and publications will be submitted to peer-reviewed journals.Trial registration number ClinicalTrials.gov (wwwclinicaltrialsgov) Registry (NCT04579315).Protocol version The protocol, version 2, has been approved by the Ethical Committee Denmark on 18 September 2020. The protocol has also been approved by Data Protection Regulation and Data Protection Law on 15 September 2020. This study protocol is in accordance with the Standard Protocol Items: Recommendations for International Trials.